QTc and anti-tuberculosis drugs: a perfect storm or a tempest in a teacup? Review of evidence and a risk assessment - Monedero-Recuero, I.; Hernando-Marrupe, L.; Sánchez-Montalvá, A.; Cox, V.; Tommasi, M.; Furin, J.; Chiang, C-Y.; Quelapio, M.; Koura, K. G.; Trébucq, A.; Padanilam, X.; Dravniece, G.; et al. (The international journal of tuberculosis and lung disease, 2018)
Multidrug-resistant (MDR) and extensively drug-resistant tuberculosis (XDR-TB) are global concerns, with stagnant treatment success rates of roughly 54% and 30%, respectively. Despite adverse events associated with several DR-TB drugs, newly developed drugs and shorter regimens are bringing hope; recent concern has focused on drugs that prolong the corrected QT interval (QTc). QTc prolongation is a risk factor for torsades de pointe (TdP), a potentially lethal cardiac arrhythmia. While QTc prolongation is used in research as a surrogate marker for drug safety, the correlation between QTc and TdP is not perfect and depends on additional risk factors. The electrocardiogram (ECG) monitoring that has been recommended when new drugs are used has created alarm among clinicians and National Tuberculosis Programmes (NTPs). ECG monitoring is often challenging in high-burden settings where treatment alternatives are limited. According to a review of studies, the prevalence of sudden death directly attributable to TdP by QTc-prolonging DR-TB drugs is likely less than 1%. The risk of death from an ineffective MDR-TB/XDR-TB regimen thus far exceeds the risk of death from arrhythmia. In patients with QTc prolongation who develop cardiac events, other significant risk factors in addition to the drugs themselves are nearly always present. Clinicians and NTPs should be aware of and manage all possible circumstances that may trigger an arrhythmia (hypopotassaemia and human immunodeficiency virus infection are probably the most frequent in DR-TB patients). We present the limited but growing evidence on QTc prolongation and DR-TB management and propose a clinical approach to achieve an optimal balance between access to life-saving drugs and patient safety.